A modified hybrid III 6-year-old dummy head model for lateral impact assessment - Rafukka, Ibrahim Abdullahi; Sahari, Barkawi; Abdul Aziz, Nuraini; Arumugam, Manohar (Hindawi Publishing Corporation, 2016)
Hybrid III six-year-old (6YO) child dummy head model was developed and validated for frontal impact assessment according to the specifications contained in Code of Federal Regulations, Title 49, Part 572.122, Subpart N by Livermore Software Technology Corporation (LSTC). This work is aimed at improving biofidelity of the head for frontal impact and also extending its application to lateral impact assessment by modifying the head skin viscoelastic properties and validating the head response using the scaled nine-year-old (9YO) child cadaver head response recently published in the literature. The modified head model was validated for two drop heights for frontal, right, and left parietal impact locations. Peak resultant acceleration of the modified head model appeared to have good correlation with scaled 9YO child cadaver head response for frontal impact on dropping from 302 mm height and fair correlation with 12.3% difference for 151 mm drop height. Right parietal peak resultant acceleration values correlate well with scaled 9YO head experimental data for 153 mm drop height, while fair correlation with 16.4% difference was noticed for 302 mm drop height. Left parietal, however, shows low biofidelity for the two drop heights as the difference in head acceleration response was within 30%. The modified head model could therefore be used to estimate injuries in vehicle crash for head parietal impact locations which cannot be measured by the current hybrid III dummy head model.